Toward a science-based classification of processed foods to support meaningful research and effective health policies - Trumbo, Paula R.; Bleiweiss-Sande, Rachel; Campbell, Jessica K.; Decker, Eric; Drewnowski, Adam; Erdman, John W.; Ferruzzi, Mario G.; Forde, Ciaran G.; Gibney, Michael J.; Hess, Julie M.; Klurfeld, David M.; Latulippe, Marie E.; et al. (Frontiers in Nutrition, 2024)
Processed foods have been part of the American diet for decades, with key roles in providing a safe, available, affordable, and nutritious food supply. The USDA Food Guides beginning in 1916 and the US Dietary Guidelines for Americans (DGA) since 1980 have included various types of commonly consumed processed foods (e.g., heated, fermented, dried) as part of their recommendations. However, there are multiple classification systems based on "level" of food processing, and additional evidence is needed to establish the specific properties of foods classified as "highly" or "ultra"-processed (HPF/UPFs). Importantly, many foods are captured under HPF/UPF definitions, ranging from ready-to-eat fortified whole grain breakfast cereals to sugar-sweetened beverages and baked goods. The consequences of implementing dietary guidance to limit all intake of foods currently classified as HPF/UPF may require additional scrutiny to evaluate the impact on consumers' ability to meet daily nutrient recommendations and to access affordable food, and ultimately, on health outcomes. Based on a meeting held by the Institute for the Advancement of Food Science and Nutrition in May 2023, this paper provides perspectives on the broad array of foods classified as HPF/UPFs based on processing and formulation, including contributions to nutrient intake and dietary patterns, food acceptability, and cost. Characteristics of foods classified as UPF/HPFs are considered, including the roles and safety approval of food additives and the effect of food processing on the food